The Relationship between Leader-Member Exchange andInnovative Work Behavior: The Mediating Role of the Voice Behavior - Sökmen, Alptekin; Mete, Edip Sabahattin (Journal of Business Research - Turk, 2021)
Purpose - This research aims to examine the mediation mechanism between leader-member exchange (LMX) and innovative work behavior (IWB) through employee voice behavior. Specifically, this research exploited the social exchange theory (SET) to examine the influence of LMX on IWB through employee voice behavior. Within this context, employees performing in higher quality LMX relationships with IWB are likely to exhibit more voice behavior. Design/methodology/approach – Self-reported questionnaires were applied to obtain data from 360 employees mainly with engineering qualifications from four companies in the defense sector in Turkey. Data were collected with a simple random sampling method in November and December 2020. Hypotheses were tested using correlation and regression analysis. The reason why the defense sector was selected for this study is the fact that the defense industry field has characteristics that make for a unique working environment. Findings - The findings show that LMX positively and significantly affects IWB and additionally voice behavior has a mediating role in this relationship. LMX had a significant influence on employee voice behavior that was ultimately associated with IWB. Finally, Voice behavior mediated the positive correlation between LMX and IWB, and stronger voice behavior boosted the indirect relationship. Discussion - This research reveals the effects of LMX and provides practical suggestions to help employees express their opinions in the organization to enhance innovation performance. Based on the SET, this research helps to understand how certain LMX which encourage high-quality exchange relationships with the supervisors and foster employee voice behaviors, may nurture employee IWBs in the organizations.